Youth’s Social Environments: Associations with Mental Problems and Achievement of Developmental Milestones in Times of Crises - Leanne A. C. van Est-Bitincka; Hilde D. Schuiringa; Paul T. van der Heijden; Marcel A. G. van Aken; Odilia M. Laceulle (Adolescents, 2023)
So far, many studies indicated that youth experience mental problems during crises, such as the COVID-19 crisis, but little attention has been paid to the relation to age-adequate functioning and its association to layered social environments. This study addresses this gap by investigating the association between social environments (i.e., household, friends, and neighbourhood) during the COVID-19 crisis with youth’s mental problems and age-adequate functioning. In total, 673 youth (mean age = 19.87, 73.4% girls) were surveyed online during the COVID-19 outbreak. In line with predictions, worse contact with household members was associated with more internalizing symptoms. A lack of privacy was associated with more internalizing and externalizing symptoms and difficulties achieving personal and school and professional milestones. Living with a vulnerable other was associated with more internalizing symptoms and difficulties achieving school and professional milestones. Worse contact with friends was associated with difficulty achieving social milestones. Additionally, neighbourhood risk moderated the association between living with a vulnerable other and school and professional milestones. A lack of privacy stood out as the most important factor associated to youth’s mental problems and achievement of developmental milestones. Future research should indicate to what extent these findings are COVID-19 crisis-specific or can generalize to other crises.